Sifat Listrik Film Tipis SrTiO3 untuk Kapasitor MOS - Darsikin Darsikin; Khairurrijal Khairurrijal; Sukirno Sukirno; Mohamad Barmawi (Institut Teknologi Bandung, 2005)
Strontium titanate (SrTiO3) film was successfully deposited on a silicon substrate by using a pulsed-laser ablation deposition (PLAD) technique. The optimum temperature is 600o C. The electrical properties measurement was metal-oxide-semiconductor capacitor. The film exhibits good insulating property at room temperature. The fixed charge density and leakage current density were also calculated. The results show that the films have promising applications as alternative gate dielectrics.